Origins of the sympathetic innervation to the nasal-associated lymphoid tissue (NALT): an anatomical substrate for a neuroimmune connection - Marafetti, Lucas E. (2014)
The participation of sympathetic nerve fibers in the innervation of the nasal-associated lymphoid tissues (NALT) was investigated in hamsters. Vesicular monoamine transporter 2 (VMAT2), an established sympathetic marker, is expressed in all neurons of superior cervical ganglia (SCG). In addition, VMAT2 -immunoreactive nerve fibers were localized in the NALT as well as in adjacent anatomical structures of the upper respiratory tract. Unilateral surgical ablation of the SCG abolished VMAT2 innervation patterns ipsilaterally while the contra lateral side is unaffected. These results provide the anatomical substrate for a neuroimmune connection in the NALT.